PENGAWASAN SERTA PEMBERIAN IZIN EDAR VAKSIN COVID 19 (SINOVAC) OLEH BPOM - Gunawan Widjaja; Septy Kusuma, Arif Rahman Baihaqi, M Ruswan Talaohu, Santika, Sarah Ramadona, Salsa Rizkya (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
This study was conducted with the aim of finding out the process of granting a distribution permit for the Sinovac Vaccine by BPOM. This research is a juridical normative research, which focuses on research on legal norms, and their implementation. The data used is secondary data, which is based on laws and regulations as primary legal material. The analysis was carried out qualitatively. The results of the study indicate that the distribution permit for Sinovac vaccine by BPOM has been carried out with great care based on the applicable legal rules